Development Strategy for Cash Waqf Linked Deposit (CWLD) For Higher Education Institutions in Bengkalis - Khalid, Ilham; Ishak, Khodijah; Hendri, Zul (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2025)
This study aims to formulate a strategy for developing Cash Waqf Linked Deposit (CWLD) in Universities in Bengkalis Regency using the Analytic Network Process (ANP) method. Based on the analysis conducted, it was found that the most priority problems are in the Nazhir aspect, especially the lack of socialization, professionalism, and certification of Nazhir. While in the Waqif aspect, the main priority is the low knowledge and awareness of prospective waqifs regarding CWLD products and the low level of trust. The prioritized solution to overcome these problems also focuses on strengthening the role of Nazhir through routine socialization, training, education, and legal assistance and supervision. On the other hand, financial literacy and waqf to Waqif are the main solutions on the community side. The most priority development strategy in the university environment is to strengthen collaboration between institutions, Nazhir training and certification, and increase CWLD literacy by Islamic financial institutions, accompanied by efforts to socialize products and increase transparency and accountability of management. This study provides an important contribution to the development of a strategic framework that can strengthen the CWLD ecosystem in the higher education environment, especially in Bengkalis Regency.